2007
DOI: 10.1164/rccm.200608-1186oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an NK1/NK2 Receptor Antagonist on Airway Responses and Inflammation to Allergen in Asthma

Abstract: Despite its demonstrated pharmacologic activity against inhaled NKA, multiple doses of AVE5883 increased the allergen-induced airway responses without affecting markers of airway hyperresponsiveness and airway inflammation. Our data question the prominent role of neurogenic inflammation in asthma and, consequently, the therapeutic potential of dual tachykinin antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 44 publications
0
39
3
1
Order By: Relevance
“…Consistently, stimulation of NK-1 receptor on immune cells resulting in activation of NF-B and proinflammatory gene expression has been de- scribed in a number of in vitro systems (2,4,44,49). Because both MCP-1 and MIP-2 have been implicated in the development of clinical and experimental asthma to which NKA has a strong pathophysiological association (13,21,33,46), our study suggests that alveolar macrophages present in the bronchioles and large airways heavily innervated by NKA-and SP-containing nerves (6,27) might be the cellular sources of these chemokines in asthma.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Consistently, stimulation of NK-1 receptor on immune cells resulting in activation of NF-B and proinflammatory gene expression has been de- scribed in a number of in vitro systems (2,4,44,49). Because both MCP-1 and MIP-2 have been implicated in the development of clinical and experimental asthma to which NKA has a strong pathophysiological association (13,21,33,46), our study suggests that alveolar macrophages present in the bronchioles and large airways heavily innervated by NKA-and SP-containing nerves (6,27) might be the cellular sources of these chemokines in asthma.…”
Section: Discussionmentioning
confidence: 72%
“…NKA, importantly, is a potent smooth muscle spasmogen in the respiratory, gastrointestinal, cardiovascular, and urinary system (10,40) and has been implicated in airway inflammatory conditions such as smoking and asthma and gastrointestinal disorders (3,6,14,27). NKA has been demonstrated to have regulatory effects on immune cells.…”
mentioning
confidence: 99%
“…The role of NK receptors and their agonistic tachykinins in allergic airway inflammation is somewhat controversial (37). In a recent study, Boot and colleagues demonstrated that a NK1/ NK2 dual antagonist failed to modulate AHR and airway inflammation after allergen challenge in patients with asthma (38). However, the role of NK receptors cannot be discounted because it is difficult to confirm blocking of all available NK receptors in the airways within such a clinical design.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to induced sputum or EBC, the clear disadvantage is that only one component from the airways is sampled even though this single biomarker is related to the underlying airway inflammation [143][144][145][146][147]. Baseline eNO levels can also aid to establish the diagnosis of asthma.…”
Section: Recommendationsmentioning
confidence: 99%